FACTORS INFLUENCING CONSUMER DECISIONS IN USING HONDA BRAND MOTORCYCLES (Case Study on Students of The Faculty of Economics Management of Universitas Pembangunan Panca Budi) - Dewi Nur Aini; Dewi Nurmasari Pane; Sakdiah; Lissia Salsabila; Muhammad Miftahul Khoiri (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
This research aims to test and know clearly how the effect of consumer motivation and quality perception on consumer decision to use Honda Motor Cycle. This research used quantitative methods that involved 60 respondents. The data was collected using questionnaires division. Data were analyzed using a statistical formula, namely by using multiple regression analysis of the processing performed by SPSS Version 16. The result of quantitative analysis showed motivation consumer and quality perception have significant influence on consumer decision to use Honda Motor Cycle